Penerapan Model Pembelajaran Blended-Problem Solving melalui Aplikasi Moodle untuk Meningkatkan Kemampuan Berpikir Kreatif Kelas XI IPA 4 SMA N 3 Surakata Tahun Pelajaran 2012/2013 - Triyanto, Samuel Agus; Prayitno, Baskoro Adi; Probosari, Riezky Maya (Universitas Sebelas Maret, 2014)
This study is aimed to improve critical thinking ability of the X-1 class of SMA N 3 Surakarta through the implementation of Blended-Problem Solving through Moodle application. This research was a classroom action research that divided into several cycles, each cycle includes four stages: planning, action, observation, and reflection. The subject of this research was the students of X-1 class at SMA N 3 Surakarta in academic year of 2012/2013. The data was obtained through the test (essay test) and non-test (interviews and documentations). And be analyzed with descriptive analytical techniques then validated by triangulation techniques. The results showed that students critical thinking ability was increased in Pre-cycle, Cycle I, and Cycle II. Critical thinking consist of six aspects are interpretation, analysis, evaluation, inference, explanation, and self-regulation. The improvement in interpretation aspect increased from 42,19% to 66,41%. Analysis aspect increased from 36,72% to 78,13%. Evaluation aspect increased from 33,59% to 78,91%. Inference aspect increased from 40,63% to 64,06%. Explanation aspect increased from 30,47% to 73,44%. Self-regulation aspect increased from 43,75% to 78,91%. The conclusion of this study explained that the implementation of Blended-Problem Solving with moodle could improve critical thinking ability of the X-1 class at SMA N 3 Surakarta.Â Key Words: Blended-Problem Solving, Moodle, Critical Thinking